The challenges of reducing tobacco use among prisoners - Richmond, R.; Butler, Tony; Indig, D.; Wilhelm, K.; Archer, V.; Wodak, A. (2012)
Issue. The prevalence of smoking among prisoners is exceptionally high and is often comorbid with alcohol and drug problems, mental illness and other health problems. This review paper summarises the literature and available research related to smoking prevalence and smoking cessation initiatives among prisoners and identifies areas of need for further research and intervention. Approach. This paper highlights three studies conducted in the New South Wales prison system which attempt to address these high rates of smoking including a feasibility study, a focus group study and a randomised controlled trial. Key Findings. The challenges of making systems-level changes to address these high rates of smoking are discussed including a recent National Summit on Tobacco Smoking in Prisons. Implications. Dissemination of research findings has assisted in highlighting the importance of tobacco smoking among prisoners and the need to develop culturally and setting appropriate smoking cessation initiatives for prisoners. Conclusions. As one of the most marginalised and socially disadvantaged populations in Australia, prisoners represent an important population to target for smoking cessation programs and interventions. This paper highlights a number of initiatives undertaken to address this problem and suggests directions for the future.[Richmond RL, Butler TG, Indig D, Wilhelm KA, Archer VA, Wodak AD. The challenges of reducing tobacco use among prisoners. Drug Alcohol Rev 2012;31:625-630] © 2012 Australasian Professional Society on Alcohol and other Drugs.